Proses dan Tahapan Akreditasi Untuk Peningkatan Kualitas Pendidikan di Sekolah Dasar dan Menengah (PDM) - Hardianti, Tuti (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2025)
The accreditation process aims to assess and improve the quality of education in schools, both public and private. The accreditation process begins with preparation, such as forming a team, socialization, training, gathering data and documents, and preparing a self-assessment report that reflects the school's condition and achievements. Next, the accreditation instrument is filled out, covering three main components: management, the educational and learning process, and facilities and infrastructure. Each component is assessed based on the quality of human resource management, curriculum, teaching methods, facilities, and other aspects that support achieving educational standards. This process not only provides recognition of the school's quality but also encourages improvement and innovation for the enhancement of educational quality. The methodology used in writing this journal combines descriptive-analytical approaches and literature studies. Accreditation results in a thorough evaluation of management, learning, and school facilities, as well as helping to identify strengths and areas needing improvement. After the field visitation, the assessment involves data verification, observations, interviews, and documentation of facilities. The assessor then analyzes the school's performance according to national education standards and produces a report containing findings, recommendations, and conclusions about the accreditation status. Finally, a meeting is held to determine the accreditation status (A, B, C, or non-accredited) and provide recommendations for improvement for schools that need to enhance their educational quality. The accreditation assessment of Basic and Secondary Education (PDM) after the visitation is that accreditation aims to evaluate and improve the quality of schools. This process includes data verification, performance analysis, and the determination of accreditation status, which serves as the basis for improvement and reaccreditation. The accreditation results provide transparency and ensure the enhancement of education quality at the primary and secondary levels.ABSTRAKProses akreditasi bertujuan untuk menilai dan meningkatkan kualitas pendidikan di sekolah, baik negeri maupun swasta. Tahapan akreditasi dimulai dengan persiapan, seperti pembentukan tim, sosialisasi, pelatihan, pengumpulan data dan dokumen, serta penyusunan laporan diri yang menggambarkan kondisi dan pencapaian sekolah. Selanjutnya, dilakukan pengisian instrumen akreditasi yang mencakup tiga komponen utama: manajemen, proses pendidikan dan pembelajaran, serta sarana dan prasarana. Setiap komponen dinilai berdasarkan kualitas pengelolaan SDM, kurikulum, metode pembelajaran, fasilitas, dan aspek lain yang mendukung pencapaian standar pendidikan. Proses ini tidak hanya memberikan pengakuan terhadap kualitas sekolah, tetapi juga mendorong perbaikan dan inovasi untuk peningkatan kualitas pendidikan. Metode penulisan jurnal ini menggabungkan pendekatan deskriptif-analitis dan studi literatur. Akreditasi menghasilkan evaluasi mendalam terhadap manajemen, pembelajaran, dan fasilitas di sekolah, serta membantu mengidentifikasi kekuatan dan area yang perlu diperbaiki. Setelah visitasi lapangan, asesmen melibatkan verifikasi data, hasil observasi, wawancara, dan dokumentasi fasilitas. Asesor kemudian menganalisis kinerja sekolah sesuai standar pendidikan nasional dan menghasilkan laporan yang berisi temuan, rekomendasi, serta kesimpulan status akreditasi. Akhirnya, rapat penetapan hasil akreditasi menentukan status (A, B, C, atau tidak terakreditasi) dan memberikan rekomendasi perbaikan bagi sekolah yang perlu meningkatkan kualitas pendidikan. Penilaian akreditasi Pendidikan Dasar dan Menengah (PDM) setelah visitasi adalah bahwa akreditasi bertujuan untuk menilai dan meningkatkan kualitas sekolah. Proses ini meliputi verifikasi data, analisis kinerja, dan penetapan status akreditasi, yang menjadi dasar perbaikan dan reakreditasi. Hasil akreditasi memberikan transparansi dan memastikan peningkatan kualitas pendidikan di tingkat dasar dan menengah.